Comparisons of Esophageal Function Tests between Chinese and British Patients with Gastroesophageal Reflux Disease - Feng Gao; Samantha Leach; Jian Yu Hao; Zhan Min Shang; Anthony Robert Hobson (Gastroenterology Research and Practice)
Objective. To investigate the esophageal function tests in British and Chinese patients with gastroesophageal reflux disease (GERD). Methods. Patients with GERD were selected from the functional gut clinic, London, and digestive department, Beijing Chao-Yang Hospital, after taking the examinations of High-resolution Manometry and Impedance (HRiM) and 24-hour Multi-Channel Intraluminal Impedance and pH Recording (MII/pH) between 2013 and 2014. Chinese healthy volunteers who undertook HRiM were also selected as control group. Results. Fifty-nine British and 82 Chinese patients with GERD and 62 Chinese healthy volunteers were entered. Values for British patients, Chinese patients, and healthy volunteers were as follows: Lower esophageal sphincter pressure (LESP) 16.0±8.6, 16.5±10.0, and 26.4±10.9 mmHg, peristalsis (normal/small break/large break) 24/12/23, 44/10/28, and 57/1/4, total bolus transit time (TBTT) 7.3±1.3, 7.6±1.2, and 6.9±0.9 s, and complete bolus transit rate (CBTR) 66.7±37.8, 61.7±36.4, and 90.3±14.0%, respectively. Stepwise linear regression analysis showed that age, gender, and ethnicity did not have significant effect on LESP, TBTT, esophageal peristalsis, and CBTR in patients with GERD. Conclusions. British and Chinese patients with GERD presented similar values of LESP, TBTT, and impaired esophageal peristalsis and CBTR.